Adenoid cystic carcinoma of the salivary glands: a pilot study of potential therapeutic targets and characterization of the immunological tumor environment and angiogenesis - Michaelides, Ioannis; Kuenzel, Julian; Ettl, Tobias; Beckhove, Philipp; Bohr, Christopher; Brochhausen, Christoph; Mamilos, Andreas (European Archives of Oto-Rhino-Laryngology, 2023)
Background: Adenoid cystic carcinoma (ACC) is a rare type of cancer commonly occurring in salivary glands. It is characterized by slow but infiltrative growth, nerve infiltration and overall poor prognosis, with late recurrence and distant metastasis. The treatment of ACC is still limited to surgery and/or (adjuvant) radiotherapy. Till now no promising systemic therapy option exists. However, various studies deliver promising results after treatment with anti-angiogenetic agents, such as anti-EGFR-antibody Cetuximab or Tyrosinkinase inhibitor Lenvatinib. Methods: By using of immunohistological methods we analyzed and compared the macrophage and lymphocyte populations, vascularization, and PD-L1-status in 12 ACC of the salivary glands. Results: All cases showed a significant elevation of macrophages with M2 polarization and a higher vascularization in ACC compared to normal salivary gland tissue. The CD4/CD8 quotient was heterogenous. ACC does not show relevant PD-L1 expression. Conclusions: The predominant M2 polarization of macrophages in ACC could be responsible for elevated vascularization, as already been proved in other cancer types, that M2 macrophages promote angiogenesis.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adenoid cystic carcinoma; Macrophage polarization; Neovascularization; Salivary gland cancer